2020
DOI: 10.3390/plants9091197
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Paclobutrazol Mediated Regulation of Growth, Upregulating Antioxidant Aptitude and Plant Productivity of Pea Plants under Salinity

Abstract: Soil salinity is the main obstacle to worldwide sustainable productivity and food security. Zinc sulfate (Zn) and paclobutrazol (PBZ) as a cost-effective agent, has multiple biochemical functions in plant productivity. Meanwhile, their synergistic effects on inducing salt tolerance are indecisive and not often reported. A pot experiment was done for evaluating the defensive function of Zn (100 mg/L) or PBZ (200 mg/L) on salt (0, 50, 100 mM NaCl) affected pea plant growth, photosynthetic pigment, ions, antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 56 publications
7
36
0
Order By: Relevance
“…Also, a significant reduction in N, P, K + , Ca 2+ , and Mg 2+ , while Na + and Clincreased were found in salinity stress conditions in faba bean plants (Abdelhamid, Shokr & Bekheta, 2010;Rady et al, 2015). The decrease of N, P, and K + was observed in common bean plants irrigated with different concentrations of NaCl, while Na + increased in tissues (Dawood, Abdelhamid & Schmidhalter, 2014;Sofy et al, 2020b). In the present study, the highest rate of P (52.5 kg ha −1 ) resulted in a significant reduction of Na + content in the shoot and root of common bean.…”
Section: Discussionmentioning
confidence: 88%
“…Also, a significant reduction in N, P, K + , Ca 2+ , and Mg 2+ , while Na + and Clincreased were found in salinity stress conditions in faba bean plants (Abdelhamid, Shokr & Bekheta, 2010;Rady et al, 2015). The decrease of N, P, and K + was observed in common bean plants irrigated with different concentrations of NaCl, while Na + increased in tissues (Dawood, Abdelhamid & Schmidhalter, 2014;Sofy et al, 2020b). In the present study, the highest rate of P (52.5 kg ha −1 ) resulted in a significant reduction of Na + content in the shoot and root of common bean.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, Zn plays a crucial role in preserving the integrity of the cell membrane [ 28 ]. It is often used to produce proteins, elongation of cells, membrane function, and environmental stress resistance [ 29 , 30 ]. Furthermore, Faizan et al [ 31 ] revealed that ZnO-NPs treatment of the tomato plant resulted in a substantial increase in growth biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…Elevation of salinity levels in the soil causes many adverse effects on barley growth because of the low osmotic potential of soil solution [ 3 ]. Salt stress induces various biochemical and physiological responses in plants and affects most of plant metabolic processes [ 1 , 4 ]. Alterations in the integrity of cell membranes [ 5 ], as well as inhibition of different enzymatic activities and photosynthesis [ 6 , 7 , 8 ], are among the main processes affected.…”
Section: Introductionmentioning
confidence: 99%